Pengaruh Motivasi Kerja dan Kemampuan Kerja Terhadap Kinerja Karyawan di Hotel Gran Surya Seririt - Nareswara, Gede Aditya; Trianasari, Trianasari (Universitas Pendidikan Ganesha, 2020)
This study aims to examine the effects of: 1) motivation on employee performance, (2) capability on employee performance, (3) motivation on capability and (4) motivation on employee performance through capability at Gran Surya Seririt Hotel. Research design used in this study was quantitative causal. The research subjects were all employees of Gran Surya Seririt Hotel with a population of 32 people. Data were collected using questionnaire and were analyzed using path analysis. The results showed that: (1) motivation has a positive and significant effect on employee performance (2) capability has a positive and significant effect on employee performance (3) motivation has a positive and significant effect on capability and (4) motivation has a positive and significant effect on employee performance through capability at Gran Surya Seririt Hotel.